Illness perceptions of adults with congenital heart disease and their predictive value for quality of life two years later. (February 2014) - Schoormans, Dounya; Mulder, Barbara JM; van Melle, Joost P; Pieper, Petronella G; van Dijk, Arie PJ; Sieswerda, Gertjan Tj; Hulsbergen-Zwarts, Mariët S; Plokker, Thijs HWM; Brunninkhuis, Leo GH; Vliegen, Hubert W; Sprangers, Mirjam AG
Background: To improve patients' quality of life (QoL) we need to identify modifiable determinants, such as illness perceptions. Patients' illness perceptions are known to regulate emotional responses and health-behaviour. Illness perceptions comprise several components: consequences, control, coherence, changeability and emotional representations. Aims: To examine (a) the relation between patient characteristics and illness perceptions, and (b) the independent predictive value of illness perceptions for future QoL. Methods: A longitudinal study in 845 patients with congenital heart disease was conducted. Patients completed three questionnaires: the IPQ-R (illness perceptions) and two years later the SF-36 and TAAQOL-CHD (QoL). Linear regression analyses were performed relating illness perceptions to patient characteristics (sex, age, disease complexity and functional status) and QoL. Results: Patients with a complex defect or poor functional status reported poor illness perceptions. Independent of patient characteristics, poor illness perceptions (i.e. a strong belief that the illness has severe consequences; a weak belief that you have a coherent illness understanding and that the illness can be controlled by treatment; and a strong belief that the illness is changeable and causes negative emotions) were predictive of future QoL. Conclusion: Illness perceptions independently predict QoL, suggesting that QoL may be improved by altering patients' beliefs about their illness. For example, increasing patients' knowledge regarding their disease and informing them about treatment opportunities may enhance their QoL.